Clinical and ultrastructural observations in a kindred with normo-hyperkalaemic periodic paralysis. Issue 1 (March 1975) - Danowski, T S; Fisher, E R; Vidalon, C; Vester, J W; Thompson, R; Nolan, S; Stephan, T; Sunder, J H
Abstract : Electron microscopic studies of muscle biopsies from clinically unaffected sibs in a family with normo-hyperkalaemic periodic paralysis with variable myotonia have revealed dilatation of the sarcoplasmic reticulum similar to that observed in affected members. This supports the view that such dilatation is not only a significant and likely primary ultrastructural change but that it may precede clinical manifestations and represent an anatomical marker of the genetic trait. Identical dilatation of the sarcoplasmic reticulum was found in the clinically unaffected father of the affected and unaffected grandchildren of the propositus. This raises the possibility that this non-consanguineous member contributed to the genetic trait or its manifestations in the grandchildren of the index patient since similar dilatation of the sarcoplasmic reticulum was not observed in the muscles of healthy control subjects.